An investigation into non-linear propagation of MSK with a view to specifying an adaptive equalizer - Howie, David Baird (Department of Electrical Engineering, 2017)
The purpose of this dissertation is to investigate the effects of non-linear propagation on a proposed digital microwave radio link which employs MSK modulation, in order to specify a suitable form of adaptive equalization. MSK is a coherent modulation technique, having improved spectral roll-off over FSK because it avoids the abrupt phase changes at the bit transitions. However computer simulations and field results indicate that MSK digital radio links do suffer from intersymbol interference and crosstalk. Software and hardware simulations of multipath propagation are based on Rummlers simplified three path model and statistics. The results obtained from the computer simulations of the MSK link and multipath propagation confirm that there is no simple relationship between the multipath parameters and the BER degradation which could be used in the design of an equalizer. The choice of adaptive equalizer is made based on criteria such as construction cost, circuit complexity, and performance improvement. It is known from ray model analysis that at a transmitting frequency of 23 GHz deep fading will only occur on links longer than 5.24 kms. However even on hops of length 5 km' s the fade time is-in the order of 1612 seconds/month (calculated using Rummlers model). A ldB increase in theoretical Eb/No will also be required to overcome potential modem imperfections. It is necessary to have a time domain equalizer which can compensate for both amplitude and phase distortions simultaneously by acting directly on the ISI. The equalizer structure chosen is a 2-by-2, fractionally spaced, decision feedback, complex adaptive equalizer with zero forcing control algorithm.